2018
DOI: 10.12688/f1000research.12802.3
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes isolated by positive and negative magnetic sorting techniques show different molecular characteristics and immunophenotypic behaviour

Abstract: Magnetic sorting of cells, based on microbead conjugated Background antibodies (Abs), employs positive as well as negative immunomagnetic separation methods, for isolation of a specific cell population. These microbeads are suggested to be nontoxic, biodegradable carriers conjugated to various antibodies. Isolation of cells through positive selection involves the attachment of antibody conjugated microbeads to the cells of interest, followed by their isolation in the presence of a strong magnetic field to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…In this study, we evaluated the functional differences of circulating monocytes, focusing particularly on their migratory activity, in AF patients who underwent catheter ablation with or without advanced LA structural remodeling gauged by echocardiography-measured LAD. In the monocyte isolation, we employed the magnet-based negative selection method to collect cells without any stimulation, since in the positive selection method the phenotype of monocytes may be altered by binding to CD14 antibody [15,16]. Moreover, we found that gene products and protein levels of CCR2 in isolated monocytes were higher in AF patients whose LAD was larger than 39 mm.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we evaluated the functional differences of circulating monocytes, focusing particularly on their migratory activity, in AF patients who underwent catheter ablation with or without advanced LA structural remodeling gauged by echocardiography-measured LAD. In the monocyte isolation, we employed the magnet-based negative selection method to collect cells without any stimulation, since in the positive selection method the phenotype of monocytes may be altered by binding to CD14 antibody [15,16]. Moreover, we found that gene products and protein levels of CCR2 in isolated monocytes were higher in AF patients whose LAD was larger than 39 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Positive selection might affect surface marker expression and cell function. Bhattacharjee and collaborators show that positive selection of CD14 + cells results in changes of cell functionality, activation and proliferation when compared to negative selection, and this difference could affect downstream applications [18] such as LPS stimuli or moDCs differentiation. The authors suggested that the temporary binding of CD14 by microbeads could affect cell activation, since this receptor is important in TLR response [18,19].…”
Section: Plos Onementioning
confidence: 99%
“…Bhattacharjee and collaborators show that positive selection of CD14 + cells results in changes of cell functionality, activation and proliferation when compared to negative selection, and this difference could affect downstream applications [18] such as LPS stimuli or moDCs differentiation. The authors suggested that the temporary binding of CD14 by microbeads could affect cell activation, since this receptor is important in TLR response [18,19]. Zhou and collaborators also observed that negative selection yields less pure cultures, but they also discussed that, in studies using moDCs a few lymphocyte contaminants were not critical as lymphocytes would not survive more than 1 week in the absence of interleukin 2 (IL-2) [20].…”
Section: Plos Onementioning
confidence: 99%
“…This method results in high purity, with typically <5% contaminating cells. However, the procedure is quite stressful for the cells, and it is unclear if monocytes change their behavior due to the labeling (Bhattacharjee, Das, Mishra, Sahay, & Upadhyay, 2017). As an alternative, negative-isolation kits are available, and these are less stressful for cells.…”
Section: Generation Of Human Osteoclasts From Purified Blood Monocytesmentioning
confidence: 99%